Penelope and the monsters - Radford, Sheri; Tripp, Christine (Montreal : Lobster Press, 2007)
Penelope won't go to sleep because she's sure there are monsters in the dark.
89809
Keywords: Monsters -- Juvenile fiction; Bedtime -- Juvenile fiction; Courage -- Juvenile fiction; Picture books for children; Monstres -- Romans, nouvelles, etc. pour la jeunesse; Heure du coucher -- Romans, nouvelles, etc. pour la jeunesse; Courage -- Romans, nouvelles, etc. pour la jeunesse; Livres d'images pour enfants; Bedtime -- Fiction; Monsters -- Fiction